2011
DOI: 10.1016/j.otsr.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty three-dimensional kinematic estimation prevision. From a two-dimensional fluoroscopy acquired dynamic model

Abstract: Analysis found some outliners in all degree of freedom with a systematic error and larger standard deviation than already published data. One should make sure that during the experiment the motion of interest is in the in-plane direction. Moreover, this study brings out the true threshold detection of this type of analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…On the contrary, Zeighami et al quantified the accuracy with simulated images from 3D models of femur and tibia virtually positioned in different configuration of flexion. We also Table 4 Accuracy of each angular and linear parameters in the current study, compared to results of 2D fluoroscopy studies [4,12,13]. reported the value of accuracy for each flexion pose.…”
Section: In Vitro Accuracymentioning
confidence: 98%
See 3 more Smart Citations
“…On the contrary, Zeighami et al quantified the accuracy with simulated images from 3D models of femur and tibia virtually positioned in different configuration of flexion. We also Table 4 Accuracy of each angular and linear parameters in the current study, compared to results of 2D fluoroscopy studies [4,12,13]. reported the value of accuracy for each flexion pose.…”
Section: In Vitro Accuracymentioning
confidence: 98%
“…Finally, it can be noticed that the semi-automatic process remained time consuming with a 90 min process for 5 poses against 20 min for 4 poses with our manual method. In the literature, several studies investigated the accuracy of the in vitro estimation of tibia and femur poses from 2D fluoroscopy associated with the 3D model against optoelectronic devices [4,12,13] (Table 4). However, the comparison to previous results must be made with care as several conditions differed.…”
Section: In Vitro Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies aimed to assess the accuracy of this shape-matching technique have reported absolute accuracies on the order of a millimeter and sub-degrees (Banks and Hodge 1996; Mahfouz et al 2003; Yamazaki et al 2004). Relative joint kinematics has reported errors of less than 2.1 degrees and 1.9 mm using a single plane fluoroscopy system (Acker et al 2011; Lebel et al 2011). It is important to note that many of these studies determine accuracy based on a foam model of the bones without soft tissue – an idealistic case without added noise from surrounding musculature and skin.…”
Section: Introductionmentioning
confidence: 99%